Animal models of monogenic migraine. (June 2016) - Chen, Shih-Pin; Tolner, Else A; Eikermann-Haerter, Katharina
Migraine is a highly prevalent and disabling neurological disorder with a strong genetic component. Rare monogenic forms of migraine, or syndromes in which migraine frequently occurs, help scientists to unravel pathogenetic mechanisms of migraine and its comorbidities. Transgenic mouse models for rare monogenic mutations causing familial hemiplegic migraine (FHM), cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), and familial advanced sleep-phase syndrome (FASPS), have been created. Here, we review the current state of research using these mutant mice. We also discuss how currently available experimental approaches, including epigenetic studies, biomolecular analysis and optogenetic technologies, can be used for characterization of migraine genes to further unravel the functional and molecular pathways involved in migraine.